(untitled) (Journal of Academic Research, 2026)
In this paper, a small geared DC motor together with a simple rotary encoder switch, module KY-040, as an angular position sensor, were modeled. A servo control system with angular position feedback is then constructed and tested both in simulation and in real-time control hardware by using MATLAB-Simulink with Arduino Mega as rapid prototyping test plat-form. To confirm the ability of the simulation to conceptualize the system’s behavior and analyze its response theoretically before practical implementation, the results of the servo control system implementation in both simulation and hardware were compared, and very similar results were obtained, as expected.